Gallbladder metastasis of renal cell carcinoma presenting as a hypervascular polypoid lesion: case report of two cases with immunohistochemical analysis - Takuya Oba; Norihiro Sato; Toshihisa Tamura; Katsushi Fujimoto; Atsuji Matsuyama; Keiji Hirata (Surgical Case Reports)
Abstract Background Metastasis of renal cell carcinoma (RCC) to the gallbladder is rare, and its clinicopathological feature remains poorly understood. We here present two cases of gallbladder metastasis from RCC presenting as a hypervascular polypoid lesion. Case presentation The first case was a 73-year-old man who had undergone right nephrectomy for clear cell RCC. Imaging studies detected a hypervascular polypoid lesion in the gallbladder 6 years after nephrectomy. Laparoscopic cholecystectomy was done. The pathological findings of the polypoid lesion showed proliferation of clear cells in the submucosal layer. Immunohistochemically, the tumor was positive for carbonic anhydrase 9 (CA9) but negative for cytokeratin 7 (CK7), suggestive of metastatic RCC. The second case was a 43-year-old man who had undergone right nephrectomy for clear cell RCC. Imaging studies revealed a hypervascular polypoid lesion of 20 mm in diameter in the gallbladder 1 year after nephrectomy. The patient underwent expanded cholecystectomy and extra-hepatic bile duct resection with lymphadenectomy. Microscopically, the polypoid lesion of the gallbladder was composed of clear cells in the submucosal layer. Immunohistochemical analysis showed positive staining for epithelial membrane antigen (EMA) and carcinoembryonic antigen (CEA) but negative staining for CK7, leading to the diagnosis of metastatic RCC. Conclusions Gallbladder metastasis from RCC is rare but should be considered when a hypervascular polypoid lesion in the gallbladder is detected during the follow-up period after RCC treatment.